Optimizing feedback reception: a scoping review of skills and strategies for medical learners - Jennifer Rowe; Diane Bouchard Lamothe; Teagan Haggerty; Jake Engel; Cole Etherington; Manvinder Kaur; Etienne Vincent; Nibras Ghanmi; Preet Gujral; Valentina Ly; Sylvain Boet (Canadian Medical Education Journal)
Background: Feedback remains essential to a learner’s professional development. Most feedback literature focuses on provision of feedback, and there is a lack of evidence-based data to support learners in developing skills to receive, evaluate and use feedback, independently of context. This scoping review mapped the literature regarding strategies and skills that optimize medical learners’ reception to feedback.